Immune Response to Mucosal Brucella Infection - López-Santiago, Rubén; Sánchez-Argáez, Ana Beatriz; De Alba-Núñez, Liliana Gabriela; Baltierra-Uribe, Shantal Lizbeth; Moreno-Lafont, Martha Cecilia (Frontiers in Immunology, 2019)
Brucellosis is one of the most prevalent bacterial zoonosis of worldwide distribution. The disease is caused by Brucella spp., facultative intracellular pathogens. Brucellosis in animals results in abortion of fetuses, while in humans, it frequently manifests flu-like symptoms and a typical undulant fever, being osteoarthritis a common complication of the chronic infection. The two most common ways to acquire the infection in humans are through the ingestion of contaminated dairy products or by inhalation of contaminated aerosols. Brucella spp. enter the body mainly through the gastrointestinal and respiratory mucosa; however, most studies of immune response to Brucella spp. are performed analyzing models of systemic immunity. It is necessary to better understand the mucosal immune response induced by Brucella infection since this is the main entry site for the bacterium. In this review, some virulence factors and the mechanisms needed for pathogen invasion and persistence are discussed. Furthermore, some aspects of local immune responses induced during Brucella infection will be reviewed. With this knowledge, better vaccines can be designed focused on inducing protective mucosal immune response.